Sistemas de cultivo do morangueiro, figueira e alface sob consórcio e monocultivo em ambiente protegido - Cecatto, Ana Paula (2012)
Producers are constantly seeking better use of their areas aiming high productivity and income, while consumers want quality food. Thus, comes the need to create and adapt alternative production systems. Intercropping between species is currently the most used among small farmers to take better advantage of available resources and consequently increase family income. In addition to using the intercropping the soilless culture is gaining space in the production systems. Accordingly, this study aimed to determine the agronomic performance of strawberry and lettuce produced in substrates and intercropped with the fig tree, and compares the yield and fruit quality of different strawberry cultivars produced in soil and substrate. To achieve this goal, the work was divided into three experiments. The study was conducted in two greenhouses at University of Passo Fundo, in the period from 12 May 2010 to 18 July 2011, including the period of the strawberry transplant until lettuce harvest. At first experiment it was determined the agronomic performance of strawberry intercropped with fig tree in a greenhouse and in the second, the lettuce crop in succession the strawberry production intercropped with fig. At the first was evaluated the strawberry cultivars Camarosa, Florida Festival, Camino Real, San Andreas, Monterey and Portola (seedlings from Argentina) and Palomar, Portola, Camarosa, Ventana and Camino Real (seedlings from Chile). At the second, lettuce cultivars Lavine Lollo Rossa, Roxa das 4 estações, Mirella, Mimosa Roxa Salad Bowl, Giovana, Pira Roxa, Pira Belíssima, Rubi and Regina. Both cultures were produced in white polyethylene bags filled with commercial substrate Tecnomax. The treatements (cultivars) were arranged in a randomized block design with five (strawberry) and four (lettuce) replications. It was evaluated yield, fruit quality and phenolic composites of strawberry and shoot: root fresh and dry mass, height, root length and volume, phenolic composites and quality in lettuce. At the third experiment it was tested production and quality of seven strawberry cultivars in two cropping systems (soil x substrate). The treatments (cultivars and cropping systems) were arranged in factorial 7 x 2. In Fig tree cv. Roxo de Valinhos was analyzed number of fruits per branch and per plant and yield. The results were analyzed by variance analysis and the means compared by Tukey's test at 5% error probability and regression. The strawberry and lettuce yield in substrate, when intercropped with the fig tree, is viable and may become more income to producers. The strawberry cv. Camarosa, independent of the origin, is an excellent source of anthocyanins, flavonoids and phenolics and the cv. from Argentina also has high yield. The lettuce cv. Lavine Lollo Rossa has high dry mass production, chlorophyll content and anthocyanins. Comparing both strawberry cropping systems the production of fruit per plant was higher when cultivated in soil while there is better quality in substrate